2015
DOI: 10.15446/caldasia.v37n2.54374
|View full text |Cite
|
Sign up to set email alerts
|

Drymonia Squamosa (Gesneriaceae), a New Species From Las Orquídeas National Natural Park (Antioquia, Colombia)

Abstract: A new species of Drymonia (Gesneriaceae) from the Cordillera Occidental of the Colombian Andes in the department of Antioquia is described and illustrated. The new species, Drymonia squamosa, is distinguished by dense clusters of scales on the petioles, glabrate leaf blades with minute punctations on the lower surface, calyx appearing swollen at base with lanceolate lobes, corolla villous to lanate, and style with glandular trichomes. Additionally, D. squamosa is categorized as vulnerable (VU) based on the IUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…or Haemoproteus spp. was similar to that established in other localities in Colombia (Rodríguez and Matta 2001 ; Valkiūnas et al 2003 ; Basto et al 2006 ; Alvarez-Londoño et al 2022 ). It has been suggested that the prevalence of these haemosporidians in birds seems to be determined by habitat characteristics (e.g., lentic water bodies, ponds, or forest type) that support the development, abundance, and diversity of their vectors or by ecophysiological traits of their hosts (González et al 2015 ; Alvarez-Londoño et al 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…or Haemoproteus spp. was similar to that established in other localities in Colombia (Rodríguez and Matta 2001 ; Valkiūnas et al 2003 ; Basto et al 2006 ; Alvarez-Londoño et al 2022 ). It has been suggested that the prevalence of these haemosporidians in birds seems to be determined by habitat characteristics (e.g., lentic water bodies, ponds, or forest type) that support the development, abundance, and diversity of their vectors or by ecophysiological traits of their hosts (González et al 2015 ; Alvarez-Londoño et al 2022 ).…”
Section: Discussionsupporting
confidence: 89%
“…sp1 (ZC1), Haemoproteus coatneyi, Haemoproteus erythrogravidus, and Haemoproteus CHLOP01 (Table S1 ). All these infections have been previously reported (Basto et al., 2006 ; Cadena, 2015 ; Cadena‐Ortiz et al., 2019 ; Doussang et al., 2019 ; González et al., 2015 ; Hussing, 2020 ; Martínez et al., 2016 ; Marzal et al., 2015 ), except for the new individuals from Chile to whom PCR, and microscopy was done in this study. Some infections could only be identified at the genus level for some individuals, leaving them as Haemoproteus sp.…”
Section: Resultssupporting
confidence: 73%
“…We investigated MHC‐I and MHC‐II genes in 93 rufous‐collared from Colombia, Ecuador, Peru and Chile, sampled in different studies from 2011 to 2018 (Basto et al., 2006 ; Cadena, 2015 ; Cadena‐Ortiz et al., 2019 ; González et al., 2015 ; Hussing, 2020 ; Martínez et al., 2016 ; Marzal et al., 2015 ) (Figure 1 , Table S1 ). Twenty‐one individuals were sampled in Colombia, 22 in Ecuador, 11 in Peru, and 39 in Chile.…”
Section: Methodsmentioning
confidence: 99%